Dressing for the Occasion? Audit Quality in the Presence of Competition for New Clients - Moser, Henrik (The Accounting Review, 2021)
ABSTRACT This paper investigates the impact of increased audit market competition on audit quality and auditor choice. I develop a model comprising two auditors who compete for a new client by choosing the audit quality for their respective existing clients and using the audited report as a signal. I identify factors that influence auditor quality decisions, as well as the behavior of clients, who potentially misstate their reports. Auditors are tempted to alter audit quality because they are eager to appear desirable from a new client's perspective. Interestingly, while recipients of the audited report adjust their conjectures about audit quality, there are conditions under which auditors lower their audit quality to increase the likelihood of being hired. The analysis extends the existing literature by describing a new approach to modeling the auditors' motivation to signal reputation for certain behavior. JEL Classifications: M40; M42; C72.